2017
DOI: 10.1016/j.apenergy.2017.03.085
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluations of solid-fueled pressurized chemical looping combustion – The effects of pressure, solid fuel and iron-based oxygen carriers

Abstract: Coal-based Pressurized Chemical Looping Combustion Combined Cycle (PCLC-CC) is the second generation of coal-fueled CLC plant, which possesses much higher plant efficiency and lower-CO 2 capture cost compare to the first generation-Coal-based CLC combined solely with steam cycle. PCLC-CC has a similar plant configuration to the Pressurized Fluidized Bed Combined Cycle (PFBC), and is composed of a PCLC Island, gas turbine, Heat Recovery Steam Generator (HRSG) and steam cycle. In the fuel reactor of PCLC Island,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Fewer studies were reported for the kinetic of solid-fuel chemical looping combustion/gasification at elevated pressure [25,33,49]. In a typical coal-based CLC system, the reactions between coal, oxygen carrier and the gasification agent (H2O or CO2) occurs as a results of various reactions as following: (6) Coal pyrolysis (Equ.…”
Section: A)mentioning
confidence: 99%
See 2 more Smart Citations
“…Fewer studies were reported for the kinetic of solid-fuel chemical looping combustion/gasification at elevated pressure [25,33,49]. In a typical coal-based CLC system, the reactions between coal, oxygen carrier and the gasification agent (H2O or CO2) occurs as a results of various reactions as following: (6) Coal pyrolysis (Equ.…”
Section: A)mentioning
confidence: 99%
“…The overall reaction rate was found to be increasing with increasing the pressure up to 5 bar then decreased at 10 bar, which was attributed to the negative effect of pressure on the coal pyrolysis stage [25]. Chen et al, [33] studied the effects of pressure on the reactivity of ilmenite and red mud OCs (red mud is a bauxite residue contains ~50% Fe2O3) on char gasification reactions using a fluidized-bed system. Fig.…”
Section: A)mentioning
confidence: 99%
See 1 more Smart Citation
“…One kilogram of mixture is enough to provide oxygen for 6.5 man-hours [47,48,49,50]. Chemical oxygen generators are the most used methods to supply oxygen in confined spaces, especially because of their long shelf life and reliability.…”
Section: How To Recycle and Produce Breathable Gases?mentioning
confidence: 99%
“…As a consequence, the studies on pressurized chemical looping operations are still very limited. 40 − 43…”
Section: Introductionmentioning
confidence: 99%